Basajiwa: Do It Yourself Innovation of Indonesian Batik Education - Jessefan Isaiah Wihewuren; Elisabeth Christine Yuwono; Vanessa Yusuf (Gelar : Jurnal Seni Budaya, 2022)
Batik as an Indonesian culture has many relations towards Indonesian traditions. Its long production process has created stigma and the youths' disinterest in batik. DIY (Do It Yourself) batik products can be the answer on how to educate and attract youths' interest in Batik Indonesia. DIY batik products are innovative and must be created to pass down batik culture to youths. Through Basajiwa and its batik DIY products, youths will be able to recognize and engage in batik culture. Motifs such as Parang Rusak, Parang Centhung, Semen Ageng Sawat Gurdha, and Kawung Sen/Beton are designed to represent some Indonesian batik motifs. The existence of DIY batik products and Basajiwa are further investigated by means of descriptive qualitative analysis research and SWOT Method. Outputs consist of facts about some Indonesian batik motifs, brand analysis of Basajiwa as DIY batik brand, and effects of DIY batik on youths. It is concluded that Basajiwa and its DIY batik products are able to be the correct solution to generate interest of youths towards batik Indonesia because it becomes a self-healing activity and to de-stress for a while.